STRATEGI GURU AKIDAH AKHLAK DALAM PEMBINAAN KARAKTER DI MADRASAH TSANAWIYAH MDIA TAQWA MAKASSAR - Wasyiah, Amwalul; Syahid, Akhmad; Mustamin; Surani; Azhar, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the strategies employed by Akidah Akhlak (Islamic Creed and Ethics) teachers to foster character development among eighth-grade students at MTs MDIA Taqwa Makassar, as well as to understand the character-building patterns applied to shape student behavior. This research employs a qualitative method with a descriptive approach. The study was conducted at MTs MDIA Taqwa Makassar, involving Akidah Akhlak teachers and eighth-grade students as subjects. Data were collected through observation, interviews, and documentation, and subsequently analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. Data validity was verified using source, technique, and time triangulation. The results indicate that Akidah Akhlak teachers employ several strategies for character development: habituation, modeling, offering counsel (mau’izah), personal approaches, and the use of rewards and punishments. Habituation is implemented through religious activities—such as reciting prayers, Tadarus (Quranic recitation), congregational prayers, and exchanging greetings—as well as by fostering polite behavior and respect for teachers and peers. Modeling involves demonstrating good behavior in daily life, while personal approaches are used to provide guidance to students facing character-related issues. The character-building pattern integrates ethical values ​​into Akidah Akhlak instruction, daily habituation, religious activities, modeling, counsel, and personal guidance. The findings reveal positive changes in student behavior, particularly regarding religiosity, honesty, responsibility, discipline, politeness, and respect for teachers. Thus, the strategies employed by Akidah Akhlak teachers play a crucial role in shaping student character, enabling students to understand, internalize, and apply ethical values ​​in their daily lives.